Engaged philosophy : essays in honour of David Braybrooke - Schotch, Peter K.; Sherwin, Susan, 1947- (University of Toronto Press, 2007)
Engaged Philosophy is an invaluable collection for anyone who has engaged with Braybrooke's writings or is interested in the future directions North American philosophy might take.